Emotional adjustment in infertile people - Ramazanzadeh, Dr fathemeh; Noorbala, Dr Ahmad Ali; Abedinia, Nasrn (Advances in Nursing & Midwifery, 2011)
Emotional adjustment in infertile people Ramazanzadeh, F.1 (MD); Noorbala, A. A.2 (MD); Abedinia, N.3* (MS) 1. Professor of Gynecology, Vali-e-Asr Reproduction Health Research Center, Imam Khomeini Hospital Complex, Tehran University of Medical Sciences, Tehran, Iran. 2. Professor of Psychiatry, Psychiatry and Psychology Research Center, Roozbeh Hospital, Tehran University of Medical Sciences, Tehran, Iran. 3. Clinical Psychologist, Vali-e-Asr Reproduction Health Research Center, Imam Khomeini Hospital Complex, Tehran University of Medical Sciences, Tehran, Iran. Abstract Background and aim Infertility has mental, social as well as reproductive consequences, among which depression, anxiety, aggressiveness, feelings of guilt, lack of self-esteem, lack of confidence, psychosomatic complaints, obsessions, relationship difficulties and sexual dissatisfaction are evident. Many authors consider the psychological consequences of infertility as responses to grief. The aim of this study was to assess emotional adjustment of infertile couples and psychological outcomes of infertility (depression, anxiety, relationship as well as sexual problems, and personality disorders) in different phases of treatment. Materials and methods The review of literature included most studies in the past 2 decades. Search terms were infertility, pregnancy, depression, anxiety, psychology disorder, marital satisfaction, psychiatric as well as psychology interventions and personality disorders in such data bases as Pub Med, Scholar, Google, Scopus and Amazon. All data were in agreement with articles published earlier than 2006 and almost all of them are accessible. Findings Most studies have found that more than half of the infertile people (women, men, and couples) learn to some extent cope with this problem. Conclusion High prevalence of psychological disorders (particularly, anxiety and depression) appears as inappropriate emotional adjustment which requires psychiatric and psychotherapeutic interventions. Keywords: Infertility, Emotional adjustment, Depression, Anxiety, In vitro fertilization (IVF). *Corresponding Author: Nasrin Abedinia. Clinical Psychologist, Vali-e-Asr Reproduction Health Research Center, Imam Khomeini Hospital Complex, Tehran University of Medical Sciences, Tehran, Iran. E-mail: abedinia_nasrin@yahoo.com